Three essays on finance - Lin, Yaheng (2015)
In essay one, we examine whether sex discrimination contributes to the underrepresentation of female executives in large corporations. China’s strong cultural preference for sons has made newborn boys greatly outnumber newborn girls. Using the male-to-female sex ratio at birth as the proxy for discrimination against women, we find that firms headquartered in more discriminatory areas hire fewer female executives. Even conditional on a woman reaching an executive position, she faces a higher likelihood of dismissal and receives lower compensation than her male counterparts. Overall, our findings suggest that sex discrimination plays an important role in preventing women from climbing the corporate ladder. In essay two, we use the abnormal white-black interracial marriage rate as the proxy for racial segmentation in the U.S. and examine whether racial segmentation contributes to the underrepresentation of minority directors in public firms. We find that firms headquartered in areas with stronger racial segmentation are less likely to have minority directors on the board. We further use the racial segmentation measure as an instrumental variable for the presence of minority directors and show that minority directors significantly increase firm’s innovation and firm value. Overall, our study provides evidence that racial segmentation plays an important role in preventing minority people from joining the boardroom. In essay three, we investigate whether some mutual funds actively trade on suppliers based on the earnings announcement return of their customers. It is well documented in the literature that the stock price of economically linked suppliers can be predictable because they do not reflect shocks to the related customers in a timely manner (Cohen and Frazzini, 2008; Menzly and Ozbas, 2010). We show that fund managers, which understand the economic linkage and trade accordingly, benefit from the trade. Moreover, these managers exhibit overall investment skills and generate superior performance. This performance results remain robust after adjusting for risk and controlling for other fund characteristics.